2016
DOI: 10.1007/s00011-016-0947-9
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory B10 cells play a protective role in severe acute pancreatitis

Abstract: Thus, we identified B10 cells as a protective factor for SAP and provided a novel target for SAP treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…Regulatory B cells suppress immune responses via the release of IL-10 or TGF-β, the inhibition of the release of IFN-γ and TNF-α and the induction of Tregs populations as well as interaction with target cells via molecules expressed on the cell surface, such as CD80, CD86 [ 18 , 26 – 30 ]. But our study showed a significant reduction in lymphocytes, CD19 + , B10 and CD19 + CD24 hi CD27 hi cells in AP patients, which was consistent with the results reported by Qiu et al [ 31 ]. Further, we detected lower MFI of CD80 and CD86 on B10 and CD19 + CD24 hi CD27 hi cells in patients with AP and CD19 + CD24 hi CD27 hi cells from AP patients suppressed the cytokine productions of CD4 + T cells and CD14 + monocytes, but the ability of CD19 + CD24 hi CD27 hi cells to induce Tregs response were impaired.…”
Section: Discussionsupporting
confidence: 93%
“…Regulatory B cells suppress immune responses via the release of IL-10 or TGF-β, the inhibition of the release of IFN-γ and TNF-α and the induction of Tregs populations as well as interaction with target cells via molecules expressed on the cell surface, such as CD80, CD86 [ 18 , 26 – 30 ]. But our study showed a significant reduction in lymphocytes, CD19 + , B10 and CD19 + CD24 hi CD27 hi cells in AP patients, which was consistent with the results reported by Qiu et al [ 31 ]. Further, we detected lower MFI of CD80 and CD86 on B10 and CD19 + CD24 hi CD27 hi cells in patients with AP and CD19 + CD24 hi CD27 hi cells from AP patients suppressed the cytokine productions of CD4 + T cells and CD14 + monocytes, but the ability of CD19 + CD24 hi CD27 hi cells to induce Tregs response were impaired.…”
Section: Discussionsupporting
confidence: 93%
“…ANP is a severe and emergent disease with multiple complications and a high mortality rate of 7% to 15%[1]. Intestinal barrier dysfunction is now considered as a major reason for the complications such as bacteria translocation and MODS in ANP.…”
Section: Discussionmentioning
confidence: 99%
“…Acute necrotizing pancreatitis (ANP) is a serious systemic disease with a mortality of 7% to 15% [1]. The intestinal barrier dysfunction plays a pivotal role in the development of ANP.…”
Section: Introductionmentioning
confidence: 99%
“…While some studies suggest that tumor-infiltrating B cells have a protective role against disease progression [ 7 12 ], other studies suggest that Bregs are upregulated in patients with solid tumor malignancies and are associated with enhanced tumor-aggressiveness and poorer prognosis [ 13 25 ]. In human lymphoid malignancies, malignant B cells appear to act as Bregs by suppressing the anti-tumor cellular immune response through expression of suppressive ligands [ 26 29 ]. This has led to successful targeting of B-regulatory functions of malignant B cells in lymphomas, which have thus far shown remarkably favorable outcomes in several clinical trials [ 26 28 ].…”
Section: Introductionmentioning
confidence: 99%